Paediatric pulmonary function testing - Hammer, Jürg; Eber, Ernst (Karger, 2005)
This book represents a comprehensive review of the most recent developments in paediatric pulmonary function testing and their clinical applications in common paediatric respiratory disorders.The first section reviews the current lung function tests used in infants and toddlers who are by nature unable to cooperate with most testing procedures. It describes the methodologies, provides normal values where available, and gives advice for data interpretation. The second section deals with the classic adult-type pulmonary function tests and their application in the semi-cooperative or cooperative older child. Age-related technical issues and the limitations of these tests are considered. Tests assessing the respiratory system beyond the usual measurements of mechanics, lung volume, and bronchial responsiveness are covered in the third section. These include the measurements of respiratory muscle function, work of breathing, diffusing capacity, and inflammatory markers in exhaled air an
Progress in respiratory research, ISSN 1422-2140 vol. 33
Keywords: pneumologie a ftizeologie; Spirometry; Respiratory Function Tests; Child; Lung Diseases; spirometrie; Infant; respirační funkční testy; Infant, Newborn; dítě; plicní nemoci; kojenec; novorozenec; pediatrie; bronchiální astma; Plethysmography; pletysmografie; Asthma